2011
DOI: 10.5090/kjtcs.2011.44.6.392
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Staged Repair of Tetralogy of Fallot with Pulmonary Atresia and a Ductus-dependent Pulmonary Circulation: Should Primary Repair Be Considered?

Abstract: BackgroundThe tetralogy of Fallot (TOF) with pulmonary atresia (PA) and a ductus-dependent pulmonary circulation (no major aorto-pulmonary collateral arteries (MAPCAs)) has been treated with staged repair or primary repair depending on the preference of surgeons or institutions. We evaluated the 19-year outcome of staged repair for this anomaly to find out whether our surgical strategy should be changed.Materials and MethodsForty-four patients with TOF/PA with patent ductus arteriosus (PDA) who underwent stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Modified BT shunt placement is one of the systemic to pulmonary shunt methods that connects the innominate or subclavian artery to ipsilateral PA with a synthetic interposition graft. It is a traditional palliative procedure used prior to complete repair for maintaining proper pulmonary blood flow and PA growth in cyanotic heart disease group, including PA VSD and TOF with severe PS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modified BT shunt placement is one of the systemic to pulmonary shunt methods that connects the innominate or subclavian artery to ipsilateral PA with a synthetic interposition graft. It is a traditional palliative procedure used prior to complete repair for maintaining proper pulmonary blood flow and PA growth in cyanotic heart disease group, including PA VSD and TOF with severe PS [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although modified BT shunt placement is still widely used for patients with ductal dependent pulmonary circulation, various studies have reported the disadvantages of modified BT shunt placement. It may increase the incidence of hypoplasia and distortion in the adjoining PA, which can lead to PA stenosis or occlusion, and when the shunt size is too big, excessive pulmonary blood flow can increase the probability of heart failure, which may require the use of diuretics or other medications to treat heart failure [ 4 , 5 ]. In addition, overshunting and shunt thrombosis can increase interstage mortality between BT shunt operation and complete surgical repair [ 5 , 6 ], with interstage mortality for infants reported to range between 10% and 15% [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(MAPCA) are candidates for primary palliation as a first step to avert hypoxia, improvement of oxygen saturation and PAs development until the complete repair [2,7, 8, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the treatment for pulmonary atresia with ventricular septal defect (PA/VSD) remains a challenge because of the heterogeneity of their pulmonary arteries and major aortopulmonary collaterals (MAPCAs) . Systemic‐pulmonary shunts (SPS) and right ventricular to pulmonary artery connection (RV‐PA connection) are the main procedures to promote pulmonary artery growth .…”
mentioning
confidence: 99%